Jurisdiction of Spanish courts over parental measures concerning a non-UE resident minor - Obergozo Miguel, Xabier (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
In this case, the Court analyses the applicability of Council Regulation 2201/2003 to determine Spanish courts´ jurisdiction in a custody case regarding a minor not domiciled in a member state (Bolivia).
Keywords: Council Regulation 2201/2003; international jurisdiction; custody/family law; Parental responsibility